New early Paleocene (Danian) paguroids from deep-water coral/bryozoan mounds at Faxe, eastern Denmark - Jakobsen, Sten L.; Fraaije, René H.B.; Jagt, John W. M.; van Bakel, Barry W.M. (Geologija, 2020)
During recent decades, decapod crustacean faunas from middle Danian (lower Paleocene) strata at Faxe (Sjælland, Denmark) have been studied in detail. However, paguroid anomurans have not yet been described formally. Two new species of hermit crab have lately been recognised in the collections of the Geomuseum Faxe. Percentages of total paguroid assemblages and feeding behaviour derived from the morphology of its chelae indicate that one of these, Dardanus faxensis sp. nov., as a generalist, was better adapted to inhabit the deep-water reefal environment of the Faxe carbonates than the more specialised, suspension-feeding Paguristes frigoscopulus sp. nov.